Dialogiczny proces rekonstrukcji. Polifonia Czesława Miłosza jako krok w stronę poetyckiej apokatastazy - Jastremski, Kim (Postscriptum Polonistyczne, 2020)
In “The Dialogic Process of Restoration: Czeslaw Milosz’s Polyphony as Movement toward Poetic Apokatastasis,” Kim Jastremski explores Milosz’s use of polyphonic poetry as a defense against nihilism in its connection of Self and Other, which has the potential to develop into poetic apokatastasis. She argues that what is typically referred to as Milosz’s polyphony is not interchangeable with the term “internal dialogue.” She typologizes Milosz’s polyphony in three subgroups: 1) poems of internal dialogue; 2) poems of external dialogue; and 3) alter ego poems.